Rector's Strategy Creates a Global Competitive Person - Achmad Ruslan Afendi; Akhmad Ramli; Sudadi Sudadi (Journal on Education, 2024)
The relocation of the capital of the archipelago to East Kalimantan provides many benefits and provides opportunities and challenges in development and encourages economic growth in the region and the surrounding region. Especially at universities in East Kalimantan and especially around the Balikpapan area. Balikpapan Institute of Technology is the only institute that has strategic importance in preparing its graduates to be able to have advantages and be able to compete globally. The Rector plays a very important role in realizing the goals of the organization he leads. To produce superior graduates with global competitiveness cannot be separated from the challenges faced and how the program is made to overcome these challenges. This study aims to describe the rector's strategy to create superior people with global competitiveness and describe the challenges faced. The type of research used is qualitative with a case study approach. The data collection method uses interviews, observations, and documentation. The results of the study stated: 1) the rector has two programs to improve community competence in the fields of technology and environment, as well as promote a holistic approach to community development in the fields of technology, environment, and economics.2) multiply research and publish in the journal Scopus, focusing on smart governance, branding, economy, life, society, and environment. And 3) empower quality assurance agencies to optimally manage community-related programs.